(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the outcomes in patients with external rectal prolapse. Study Design: Observational study Place and Duration of Study: This study was conducted at the Department of General Surgery, Bhatti International Teaching Hospital and Central Park Hospital, Lahore from 01-06-2016 to 30-11-2017. Materials and Methods: Thirty patients above age of 12 years both males and females with complete rectal prolapse were included. Patients who were below the age of twelve years, recurrent prolapse, colorectal cancer, with medical issue like renal failure, acute disease of liver were excluded. Patients with lower gastrointestinal symptoms e.g. pain, something coming out from anus, bleeding per rectum and tenesmus were diagnosed on history basis and examination. Resection, Wells rectopexy and thieresch stitch was performed in patients Results: There were 22 (73.33%) male patients and 8 (26.67%) female patients. Wells Rectopexy was done in 25 patients, thieresch stitch was applied in 2 patient and 3 patients had anterior resection. Post-operative complications such as pelvic abscess found in 2 (6.67%), constipation in 6 (20%) patients and wound infection in 2 (6.67%) patients. Recurrence found in 1 (3.33%). No mortality was recorded. Conclusion: The Wells rectopexy was the safe and effective procedure with very low rate of complications.